A comparative study of academic libraries websites in Malaysia / Abd Rashid Abdullah - Abdullah, Abd. Rashid (2001)
The comparative study, which have been done on eight academic library websites in Malaysia have shown that most of the library are ready to give their online services to the users. Most of them are fulfilled the criteria which are needed in building websites. Based on this research, University Malaya Library website has been selected the best library websites as compared to others.